SMALL BUSINESS AS THE MAIN FACTOR OF ECONOMIC DEVELOPMENT - M. M. Dadaboyeva (Modern American Journals, 2025)
This paper highlights the role of small businesses in the modern economy and their impact on economic development. It analyzes the contribution of small enterprises to job creation, the stimulation of innovation, the activation of regional economies, the promotion of a competitive environment, and the increase in tax revenues to the state budget. The study substantiates that sustainable economic growth can be achieved through the development of small businesses. This work considers small business as a strategic factor in economic progress and emphasizes the need to strengthen its position in state policy.
Keywords: Small business, economic development, entrepreneurship, job creation, innovation, regional development, tax revenue, competitiveness, sustainable growth.